Circulation stabilizing therapy and pulmonary high‐resolution computed tomography in a porcine brain‐dead model. Issue 1 (7th August 2015) - Bozovic, G.; Steen, S.; Sjöberg, T.; Schaefer‐Prokop, C.; Verschakelen, J.; Liao, Q.; Höglund, P.; Siemund, R.; Björkman‐Burtscher, I. M.
Abstract : Background: Currently 80% of donor lungs are not accepted for transplantation, often due to fluid overload. Our aim was to investigate if forced fluid infusion may be replaced by a new pharmacological therapy to stabilize circulation after brain death in an animal model, and to assess therapy effects on lung function and morphology trough blood gas parameters and state‐of‐the‐art High‐resolution CT (HRCT). Methods: Brain death was caused by surgical decapitation. To maintain mean aortic pressure > 60 mmHg, pigs were treated with forced electrolyte solution infusion (GI; n  = 6) or the pharmacological therapy (GII; n  = 11). GIII ( n  = 11) were non‐decapitated controls. Lung function was investigated with blood gases and lung morphology with HRCT. Results: GI pigs became circulatory instable 4–6 h after brain death in spite of forced fluid infusion, five pigs showed moderate to severe pulmonary edema on HRCT and median final PaO2 /FiO2 was 29 kPa (Q1; Q3; range 26; 40; 17–76). GII and GIII were circulatory stable (mean aortic pressure > 80 mmHg) and median final PaO2 /FiO2 after 24 h was 72 kPa (Q1; Q3; range 64; 76; 53–91) (GII) and 66 kPa (55; 78; 43–90) (GIII). On HRCT, only two pigs in GII had mild pulmonary edema and none in GIII. More than 50% of HRCT exams revealed unexpected lung disease even in spite of PaO2 /FiO2 > 40 kPa. Conclusion: Pharmacological therapy but not forced fluid infusion prevented circulatory collapse and extensive HRCT verified pulmonary edema after acute brain death. HRCT was useful to evaluate lung morphology and revealed substantial occult parenchymal changes justifying efforts toward a more intense use of HRCT in the pre‐transplant evaluation.